(untitled) (Research, Society and Development, 2022)
This work is the result of one of the activities of the Training Assistant Course of CBMERJ and aimed to analyze critically the Film “The Day of the Attack” and discuss expert actions that are addressed during the film from the perspective of Brazilian expertise. Methods: This is a qualitative research of the type Critical Review of Film and written in eight steps: identification of the work, Identification of the author of the film, presentation of the work, description of the structure, writing on the content, critical analysis of the object of the film, recommendation to the audience of interest and identification of the designer. Results and discussion: after watching the film, it was possible to discuss the scene where there is the explosion in the Boston Marathon, and bring elements of Brazilian legislation and literature that corroborate the actions of the film. Final Considerations: it was possible to visualize through the film some stages of the process of expertise, the need to invest in the psychological approach of the agents in charge of investigations, the valorization of the Nurse as a pre-hospital care professional and co-responsible for the preservation of traces and maintenance of the chain of custody, and the critical review is a relevant pedagogical action in the scientific development of the student of the Auxiliary Skills Course.